Diversity and Homogeneity among Small Plasmids of Aeromonas salmonicida subsp. salmonicida Linked with Geographical Origin - Attéré, Sabrina A.; Vincent, Antony T.; Trudel, Mélanie V.; Chanut, Romain; Charette, Steve J. (Frontiers in Microbiology, 2015)
Furunculosis, which is caused by Aeromonas salmonicida subsp. salmonicida, is a major salmonid disease in fish farms worldwide. Several plasmids found in this bacterium confer phenotypes such drug resistance and virulence. Small plasmids (pAsa1, pAsa2, pAsa3, and pAsal1) related to ColE1- and ColE2-type replicons are usually present in its normal plasmidome. In the present study, with the objective to investigate if these plasmids display particularities related to the origin of the isolates bearing them, a total of 153 isolates, including 78 new and 75 previously described, were analyzed for the presence of small plasmids by PCR and DNA restriction fragment profiling. A geographical dichotomy between Canadian and European isolates for their propensity to do not have pAsa3 or pAsal1 was found. In addition, the genotyping analysis led to the identification of two European isolates harboring an unusual pAsal1. An investigation by next-generation sequencing (NGS) of these two isolates shed light on two pAsal1 variants (pAsal1C and pAsal1D). As with pAsal1B, another pAsal1 variant previously described, these two new variants bore a second insertion sequence (ISAS5) in addition to the usual ISAS11. The characterization of these variants suggested that they could predominate over the wild-type pAsal1 in stressful conditions such as growth at temperatures of 25°C and above. To obtain a comprehensive portrait of the mutational pressure on small plasmids, 26 isolates whose DNA had been sequenced by NGS were investigated. pAsa3 and pAsal1 were more prone to mutations than pAsa1 and pAsa2, especially in the mobA gene, which encodes a relaxase and a primase. Lastly, the average copy number of each plasmid per cell was assessed using raw sequencing data. A clear trend with respect to the relative proportion per cell of each plasmid was identified. Our large-scale study revealed a geographical dichotomy in small plasmid repertoire in addition to a clear trend for pAsa3 and pAsal1 to be more frequently altered. Moreover, we present the discovery of two new variants of pAsal1: pAsal1C and pAsal1D.